Pendampingan Pengelolaan Keuangan Rumah Tangga Islami pada Guru SMKN 01 di Kabupaten Siak - Yessi Nesneri; Irdayanti Irdayanti; Anna Nurlita (Lembaga penelitian dan pengabdian kepada masyrakat, 2020)
Islamic household financial management is one of the important things that must be done by every Muslim household, in helping to create a harmonious family. Assistance in Islamic household financial management at SMKN 01 teachers in Siak Regency aims to increase public knowledge about Islamic household financial management in accordance with the concept of Islamic finance. Community service activities begin with preparation for implementation, namely by surveying the school by providing a schedule of activities and materials to be discussed with teachers. Activities are carried out using lecture and discussion methods as well as the practice of making Islamic financial planning. The material is in the form of an explanation of the concept of Islamic household financial management. Steps to manage finances based on Islamic concepts, as well as the practice of making financial planning in accordance with islamic financial management.